Carotid stenting for unilateral stenosis can increase contralateral hemispheric cerebral blood flow. (12th July 2017) - Sadato, Akiyo; Maeda, Shingo; Hayakawa, Motoharu; Adachi, Kazuhide; Toyama, Hiroshi; Nakahara, Ichiro; Hirose, Yuichi
Abstract : Background: The revascularization of carotid stenosis can increase ipsilateral cerebral blood flow (CBF). Occasionally, elevated CBF is also evident on the contralateral side, but this phenomenon is poorly understood. Objective: To analyze retrospectively the relationship between a contralateral CBF increase and several clinical and radiologic features. Materials and methods: We retrospectively analyzed 40 patients with unilateral cervical carotid stenosis treated by carotid artery stenting (CAS). Using 123 I-iodamphetamine single-photon emission computed tomography (SPECT); we compared pre- and postoperative hemispheric CBF on both sides. We investigated the influence of the following five factors on the increase of the contralateral hemispheric CBF: stenosis grade (≥50% or <50%, according to the North American Symptomatic Carotid Endarterectomy Trial criteria); age; the presence of anterior and posterior communicating arteries; postoperative hyperperfusion on the stenotic side; and the presence of cerebral steal phenomenon during preoperative acetazolamide-challenge SPECT. Results: Following unilateral CAS, mean hemispheric CBF increased significantly on both sides: from 33.4±5.6 (mean ± SD) to 38.7±7.8 mL/min on the operated side (paired t test, p<0.001) and f35.4±5.4 to 39.2±7.2 mL/min on the contralateral side (p<0.001). In a general linear model, stenosis grade (≥50%) alone was significantly correlated with the increase of the CBF on the contralateral side (p=0.03). Conclusion: Revascularization by CAS for unilateral carotid stenosis can increase hemispheric CBF on both sides. Increase of the contralateral CBF is correlated with stenosis grade (≥50%).